1990
DOI: 10.3109/08916939008993366
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: Cell-Mediated Immunity to Human Brain Gangliosides

Abstract: Cell-mediated immunity (CMI) to myelin components has been implicated in Multiple Sclerosis (MS) pathogenesis: two targets were suggested, Myelin Basic Protein with controversial results and, more recently, gangliosides. In order to investigate their possible involvement, we have performed Leukocyte Migration inhibition (LMI) tests in the presence of human brain gangliosides. Thirty nine MS patients (twenty four being "definite", according to McDonald and Halliday's classification), twenty nine patients with O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Convincing evidence that immune responses against gangliosides may indeed cause axonal degeneration has been provided by the induction of experimental sensory ataxic neuropathy in rabbits by immunization with GD1b, a ganglioside found in dorsal root ganglion neurons and dorsal root axons. 3 Several studies have found increased antiganglioside antibody levels in the sera and/or cerebrospinal fluid (CSF) of patients with MS. 4,5,6,7,8,9,10,11,12,13 Acarin et al 11 and Sadatipour et al 12 compared the levels among the subtypes of MS and showed increased antiganglioside antibody levels in patients with primary progressive MS. Several studies have also demonstrated increased peripheral blood T lymphocyte responses to mixed ganglioside preparations in patients with MS. 14,15,16,17,18 However, there have been no studies comparing T cell reactivity to individual gangliosides among the relapsing-remitting, secondary progressive and primary progressive forms of MS. The present study was performed to determine the T cell responses to individual gangliosides in the different forms of MS. We found increased peripheral blood T cell proliferative responses to GM3 and GQ1b gangliosides in patients with primary progressive MS.…”
Section: Introductionmentioning
confidence: 99%
“…Convincing evidence that immune responses against gangliosides may indeed cause axonal degeneration has been provided by the induction of experimental sensory ataxic neuropathy in rabbits by immunization with GD1b, a ganglioside found in dorsal root ganglion neurons and dorsal root axons. 3 Several studies have found increased antiganglioside antibody levels in the sera and/or cerebrospinal fluid (CSF) of patients with MS. 4,5,6,7,8,9,10,11,12,13 Acarin et al 11 and Sadatipour et al 12 compared the levels among the subtypes of MS and showed increased antiganglioside antibody levels in patients with primary progressive MS. Several studies have also demonstrated increased peripheral blood T lymphocyte responses to mixed ganglioside preparations in patients with MS. 14,15,16,17,18 However, there have been no studies comparing T cell reactivity to individual gangliosides among the relapsing-remitting, secondary progressive and primary progressive forms of MS. The present study was performed to determine the T cell responses to individual gangliosides in the different forms of MS. We found increased peripheral blood T cell proliferative responses to GM3 and GQ1b gangliosides in patients with primary progressive MS.…”
Section: Introductionmentioning
confidence: 99%
“…Again, the specific T-cell activity was increased most markedly during attacks of MS. Next, Bellamy et al [ 158 ] found that two T-cell lines (one CD4 + and the other CD8 + ), derived in the presence of IL2, but absence of antigen, from cerebrospinal fluid (CSF) of patients with progressive MS, subsequently responded most strongly to gangliosides. Using the leukocyte migration inhibition assay, Beraud et al [ 159 ] also showed that T cells from MS patients undergoing an attack (compared to T cells from patients in remission or from controls) showed increased migration inhibition when incubated in the presence of human brain gangliosides.…”
Section: T-cell Responses To Myelin Proteolipids and Glycolipids Imentioning
confidence: 99%
“…Several studies have found increased anti-ganglioside antibody levels in the sera and/or cerebrospinal fluid of patients with MS [15][16][17]. Acarin et al [18] and Sadatipour et al [19] compared the levels among the subtypes of MS and showed increased anti-ganglioside antibody levels in patients with primary progressive MS. Several studies have also demonstrated increased peripheral blood T lymphocyte responses to mixed ganglioside preparations in patients with MS [20,21]. Other researchers found increased circulating T cell reactivity to GM3 and GQ1b in primary progressive MS raising the possibility that ganglioside-specific T cells may contribute to the pathogenesis of axonal damage in primary progressive form of MS [22].…”
Section: Introductionmentioning
confidence: 99%